PENGARUH FEAR OF MISSING OUT (FOMO) DAN GAYA HIDUP BERBELANJA TERHADAP IMPULSE BUYING DENGAN LITERASI KEUANGAN SEBAGAI VARIABEL MODERASI PADA MAHASISWA PENDIDIKAN EKONOMI FAKULTAS EKONOMIKA DAN BISNIS UNIVERSITAS NEGERI SEMARANG ANGKATAN 2022 PENGGUNA E-C - Ammaryafi, Farisy; Aulia Pambajeng Miftahunnajah, Nimas (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the phenomenon of increasing impulse buying behavior among college students using e-commerce, which indicates a gap between financial cognition and actual consumption behavior. The purpose of this study is to examine and analyze the effect of Fear of Missing Out (FOMO) and shopping lifestyle on impulse buying, as well as to examine the role of financial literacy as a moderating variable. A quantitative approach with a correlational design was applied to the population of Economics Education students at Universitas Negeri Semarang class of 2022. The purposive sampling technique was used to determine a sample of 80 respondents. Data were collected through an online questionnaire using a Likert scale, and analyzed using Partial Least Squares - Structural Equation Modeling (PLS-SEM) and Moderated Regression Analysis (MRA). The results prove that FOMO and shopping lifestyle have a significant positive effect on impulse buying, with shopping lifestyle being the most dominant predictor. Another crucial finding shows that financial literacy is unable to moderate (weaken) the effect of FOMO and shopping lifestyle on impulse buying. This confirms the occurrence of a cognitive-behavioral gap, where students' theoretical understanding of financial management has not transformed into effective self-control in dealing with affective and sociocultural stimuli in the digital era. This study recommends the need for a reorientation of financial education that emphasizes behavioral finance.